Understanding identity in the musical SIX - Craven, Rebecca (2024)
SIX is a musical retelling of the lives of the six wives of Henry VIII, but as they say themselves, are the stories we know really the truth? This work will look at the way in which identity is seen throughout the musical. Firstly, the work will consider what the identity of the show is as a whole, thinking about the function the show was created for and then relating to the study of two types of musical theatre: the integrated music and the concept musical. In doing so, some key shows within those areas will be discussed including Oklahoma! (1943), Company (1970), and A Chorus Line (1975). Following this, the idea of identity related to the characters, the six wives of Henry VIII will be explored, firstly the identity they have historically and then the identity that the show has crafted for them. These new personas will be looked at in terms of their individual songs and the influences of existing artists. Finally, the piece will look at the identities of the individuals cast to portray the Queens, and how their identities influence the roles they play.